Seedling production of Ceiba speciosa in different volume of tubes using biosolids as substrate - Lima Filho, Pedro; Santos Leles, Paulo Sergio dos; Marques de Abreu, Alan Henrique; Silva, Eduardo Vinicius da; Fonseca, Aline Cassia da [UNESP] (Centro Pesquisas Florestais, Ufsm, 2019)
One of the problems encountered in the formation of stands aimed at forest restoration is the quality of the seedlings. The objective of this study was to evaluate the different volumes of tubes for the seedling production of Ceiba speciosa, using biosolids as a substrate. The experiment consisted of the seedlings production stage and evaluation of the performance in the field. The treatments were the tubes of 55, 110, 180 and 280 cm(3). Both phases of this experiment were installed in a completely randomized design, with the stage of seedling production composed by four repetitions of 12 plants, and field stage composed by 20 seedlings from each treatment, with height and diameter closer to the average for the last assessment carried out in the nursery. Using biosolids as the main component of the substrate for the production of Ceiba speciosa seedlings, and for the site conditions where the forest stand was implanted, it is recommended to use the 110 m(3) tube, because in this tube occurred growth similar to plants in the tubes of larger volumes, resulting in lower volume of substrate, smaller area occupied in the seed-plot and greater ease of transport and handling.
Keywords: Sewage sludge; Seedlings quality; Forest restoration; Ceiba